Quantification of Bcl-2/Bax genes in A549 Lung Cancer Cell Lines Treated with Heptamethoxy Flavones - Swarnalatha, Y. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Heptamethoxy flavones (HMF)isolated from Sphaeranthus amaranthoides can bring inhibitory result on the growth of lung adenocarcinoma cells. However, very few studies have demonstrated a relative effect of the HMF on A549 cells. This study aims to investigate the underlying molecular mechanisms involved in the therapeutic activity of HMF in human lung adenocarcinoma cells. Materials and Methods: HMF was isolated from S. amaranthoides using column chromatography, and the structure was elucidated using nuclear magnetic resonance studies. The cytotoxicity was assessed using MTT assay, and the morphological change was observed by performing dual staining (ethidium bromide/acridine orange). The integrity of nuclear membrane was investigated using propidium iodide staining, and the apoptosis proteome was also assessed. The levels of proliferative and apoptotic genes were quantified using quantitative polymerase chain reaction. Finally, apoptosis was confirmed with the cell cycle analysis using flow cytometry. Results: The cells were maintained in the exponential phase by optical cell count, and HMF showed the half maximal inhibitory concentration value of 83.67 μg/mL. Morphological changes of cell and the nucleus proved the apoptosis with evidence of blebbing and chromatin condensation. The cell cycle analysis includes an accumulation of the cells in G1–G0 and less number of cells at other stages of cell cycle. The enhanced levels of apoptotic gene (caspase-3 and Bax with GAPDH) expression and lowered levels of Bcl-2 (proliferative gene) expression were triggered through intrinsic and extrinsic pathways during apoptosis. Interpretation and Conclusion: It is concluded that the HMF isolated from S. amaranthoides was induced apoptosis through Bcl-2/Bax signaling pathways with the involvement of caspase-3 at G1–G0 cell cycle arrest.